2023
DOI: 10.3390/ijms241713165
|View full text |Cite
|
Sign up to set email alerts
|

C-H Groups as Donors in Hydrogen Bonds: A Historical Overview and Occurrence in Proteins and Nucleic Acids

Zygmunt Stanislaw Derewenda

Abstract: Hydrogen bonds constitute a unique type of non-covalent interaction, with a critical role in biology. Until fairly recently, the canonical view held that these bonds occur between electronegative atoms, typically O and N, and that they are mostly electrostatic in nature. However, it is now understood that polarized C-H groups may also act as hydrogen bond donors in many systems, including biological macromolecules. First recognized from physical chemistry studies, C-H…X bonds were visualized with X-ray crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…Some recent papers have suggested that a direct nonclassical hydrogen bond between Ade:C2 and Thy:O2 may account for part of the stability of Watson–Crick and Hoogsteen A·T pairs. This suggestion was based on the experimental vibrational frequency measurement of the O2-containing carbonyl group in Thy and its solvatochromatic shift in duplex DNA as well as theoretical calculations of vibrational signatures of A·T pairs in vacuum. While vibrational shifts suggest that the O2 carbonyl may be involved directly in the A·T pair, they may also arise from interaction with weakly bound water molecules in the minor groove .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some recent papers have suggested that a direct nonclassical hydrogen bond between Ade:C2 and Thy:O2 may account for part of the stability of Watson–Crick and Hoogsteen A·T pairs. This suggestion was based on the experimental vibrational frequency measurement of the O2-containing carbonyl group in Thy and its solvatochromatic shift in duplex DNA as well as theoretical calculations of vibrational signatures of A·T pairs in vacuum. While vibrational shifts suggest that the O2 carbonyl may be involved directly in the A·T pair, they may also arise from interaction with weakly bound water molecules in the minor groove .…”
Section: Results and Discussionmentioning
confidence: 99%
“…CH•••O H-bonding has been debatable; however, quantum studies have characterized them as weaker and with minute directionality than the conventional H-bonds [83]. In structural biology, these bonds were only appreciated about 40 years ago, with immense contributions to the structural integrity of biomolecules, recognition and binding, and catalysis [84,85]. In conclusion, Pandit and colleagues found that two types of complexes exist in each mixture of dilauroylphosphatidylcholine (DLPC): cholesterol and (DPPC): cholesterol, exhibiting stoichiometries of 1:1 and 2:1; however, the DLPC: cholesterol was more populated with species of a 1:1 ratio and vice versa for the DDPC: cholesterol.…”
Section: Computational Tools In the Design Of Liposome-based Drug Del...mentioning
confidence: 99%
“…Evolution can also change the hydrogen bond donor to a weaker variant to attain the same effect, for example replacing O–H with S–H or even acetylenic C–H or other C–H groups (e.g. 109 ). Pharmaceutical chemistry cannot engineer the protein to which the drug has to bind, so modification of proteins by introducing weaker H-bonds is a path open to evolution but not to technology, which is why human industry prefers the use of fluorine as a weak H-bond acceptor.…”
Section: Potential Interdictors Of Fluorine As a Major Component Of B...mentioning
confidence: 99%